Pengaruh Kualitas Produk Terhadap Citra Merek Pada Apotek Maggha Mulia 2 di Kota Palembang - Jennifer Queensly Tumbilung Queensly Tumbilung; Retno Budi Lestari (MDP Student Conference, 2026)
This study aims to analyze the effect of product quality on brand image at Maggha Mulia 2 Pharmacy in Palembang City. The study used a quantitative approach by distributing questionnaires to 170 respondents who had purchased drugs at the pharmacy. The sampling technique used non-probability sampling with a purposive sampling approach. The research instrument used a Likert scale and the data were processed with SPSS version 26. The results of a simple linear regression analysis showed that product quality had a positive and significant effect on brand image. The better the product quality provided, the more positive the pharmacy's brand image in the eyes of customers. This study proves the importance of maintaining product quality to strengthen the brand image at Maggha Mulia 2 Pharmacy.